Microwave-Assisted Pyrolysis Process of Sengon Sawdust by Using Ni/Al2O3 Catalyst: Proses Pirolisis Berbantuan Gelombang Mikro Serbuk Gergaji Sengon Laut Dengan Katalis Ni/Al2O3 - Wulandari, Lisa Ayu; Azis, Muhammad Mufti (Universitas Muhammadiyah Sidoarjo, 2023)
Microwave-assisted pyrolysis (MAP) process is one of the alternative biomass pyrolysis processes currently being developed. This process aims to increase the yield of bio-oil and reduce residues during the pyrolysis process. One of the challenges faced in this process is the low thermal conductivity of the biomass which will also affect the quality of the bio-oil produced. The addition of a catalyst is intended to increase the yield of bio-oil and the quality of bio-oil. In addition, this process is also carried out by adding an absorber to increase the thermal conductivity of the biomass. Ni/Al2O3 catalyst was synthesized by wet impregnation method with variations of 8%, 11% and 12.5% ​​nickel loading. Furthermore, the catalyst was mixed with sawdust of sengon (Paraserianthes falcataria) and coconut charcoal as absorber. The microwave is set at a maximum temperature of 500 °C with an operating time of 60 minutes. Pyrolysis results showed that the addition of catalyst and absorbent was able to increase bio-oil production, with the percentage of bio-oil being 25.2%, 27%, and 33% respectively compared to pyrolysis without catalyst which only reached 11%. GC-MS analysis of bio-oil showed various hydrocarbon components in each variation, with the main components being phenol and benzene.